Cecal growth factors promote enteric neurosphere formation and hindgut colonization in the avian model - Soós, Ádám; Szőcs, Emőke; Halasy, Viktória; Gecse, Zsanna; Mógor, Fruzsina; Jurenka, Csenge; Kocsis, Katalin; Mucksová, Jitka; Hejnar, Jiří; Nagy, Nándor (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe enteric nervous system (ENS) originates from neural crest cells (NCC) that migrate along the developing gut and differentiate into enteric neurons and glial cells. Disruption of ENS development leads to neurointestinal disorders, such as Hirschsprung disease (HSCR), characterized by aganglionic segments in the distal colon. ENS-derived stem cells (ENSCs), capable of forming multipotent neurospheres, have shown great promise for cell-based therapies. However, optimizing the cell culture conditions and understanding the molecular signals that regulate ENSC development remain unclear. Given the conserved developmental interactions between NCCs and the gut mesenchymal environment in mammals and birds, the avian embryo provides a valuable model for investigating ENS development.MethodsIn this study, we developed and characterized an avian model system for generating enteric neurospheres from transgenic mCherry-labeled chick gut tissue.ResultsAddition of GDNF, WNT11, endothelin-3, and the BMP inhibitor Noggin (GWEN medium) resulted in significantly larger and more numerous neurospheres compared to control cultures. Immunostaining showed that GWEN-treated neurospheres contained abundant SOX10+ glial precursors, HU + neurons, and SOX10+/PHOX2B+/HU- progenitors, indicating both differentiation and maintenance of stem cells. When plated on a fibronectin-coated surface in the presence of GDNF, cells from GWEN-treated neurospheres migrated a longer distance and extended more βIII-tubulin + neurites than controls, demonstrating enhanced neurogenic potential. Using ex vivo recombination assays and chorioallantoic membrane transplantation, we demonstrate that E12 mCherry+ neurospheres pre-cultured in GWEN medium migrate extensively and form enteric ganglia within host hindgut tissue.ConclusionThese findings support the neurosphere-forming potential of avian ENSCs and identify ceca-derived signals (GDNF, WNT11, ET-3) and Noggin as potent regulators of ENS progenitor maintenance and differentiation.